2003
DOI: 10.1096/fj.03-0069fje
|View full text |Cite
|
Sign up to set email alerts
|

IL‐1 induced release of Ca2+from internal stores is dependent on cell‐matrix interactions and regulates ERK activation

Abstract: The cellular mechanisms that modulate interleukin-1 (IL-1) signaling are not defined. In fibroblasts, IL-1 signaling is affected by the nature of cell-matrix adhesions including focal adhesions, adhesive domains that sequester IL-1 receptors. We conducted studies to elucidate which steps of cellular Ca2+ handling are affected by focal adhesions and by which mechanisms focal adhesions modulate IL-1-induced Ca2+ signals and ERK activation in human gingival fibroblasts. Cells were plated on poly-l-lysine or fibro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 41 publications
1
37
1
Order By: Relevance
“…It has been reported that IL-1 may cause Ca 2ϩ release from intracellular stores through cell-matrix interactions in fibroblasts spread on surfaces coated with fibronectin (Wang et al, 2003). In isolated normal sigmoid muscle cells, however, we did not find that IL-1␤ caused cytosolic Ca 2ϩ increase under our experimental conditions.…”
Section: Discussioncontrasting
confidence: 85%
“…It has been reported that IL-1 may cause Ca 2ϩ release from intracellular stores through cell-matrix interactions in fibroblasts spread on surfaces coated with fibronectin (Wang et al, 2003). In isolated normal sigmoid muscle cells, however, we did not find that IL-1␤ caused cytosolic Ca 2ϩ increase under our experimental conditions.…”
Section: Discussioncontrasting
confidence: 85%
“…IL-1␤ may induce the synthesis of ET-1 (12,32), which has also been demonstrated to act as an inducer of proinflammatory cytokines, and both ET-1 and IL-1␤ are capable of activating ERK1/2 ( Fig. 7) (60,65,66). In addition, cyclin D1, an important mediator of cell proliferation, is a downstream target of ERK1/2 and ET-1 (49,66).…”
Section: Discussionmentioning
confidence: 99%
“…The deletion of SHP-2 by siRNA or by homologous recombination showed that SHP-2 is indeed required for both processes because IL-1-induced PLC␥1 phosphorylation and calcium release were almost completely blocked. We also tested whether calcium release, which is downstream of IL-1-induced SHP-2 and PLC phosphorylation, might affect these events, possibly by a negative feedback system involving the formation and functional attributes of focal adhesions (18). This notion was examined in cells that had been preincubated with BAPTA/AM to reduce IL-1-induced alterations of [Ca 2ϩ ] i .…”
Section: Discussionmentioning
confidence: 99%
“…However, the mechanisms whereby the various participants in this signaling pathway are marshaled to specific sites within the cell are not known. As noted earlier, IL-1-induced ERK activation is focal adhesion-restricted (9), requires the release of Ca 2ϩ from the endoplasmic reticulum (18), and may depend on the sequestration of signaling molecules such as Ras to endoplasmic reticulum membranes (17). Accordingly, we considered that focal adhesions and the endoplasmic reticulum may provide spatially discrete staging sites (19) that enable the SHP-2-dependent activation of ERK by IL-1.…”
Section: Interleukin-1 (Il-1)mentioning
confidence: 93%
See 1 more Smart Citation